An RBC model with Epstein-Zin (non-expected-utility) recursive preferences: lessons from Bulgaria (1999-2018) - VASILEV, Aleksander (Journal of Mathematical Economics and Finance; Vol 7 No 1 (2021): JMEF, Volume VII, Issue 1(12), Summer 2021, 2021)
We introduce Epstein-Zin (1989, 1991) preferences into a real-business-cycle (RBC) model with government. We calibrate the model economy to Bulgarian data for the period after the currency board regime (1999-2018). We evaluate the quantitative importance of the presence of ”early resolution of uncertainty” motive for the propagation of cyclical fluctuations in Bulgaria. Allowing for Epstein-Zin preferences improves the model performance against data, and in addition this extended setup dominates the standard RBC model framework, e.g., Vasilev (2009).